Rancang Bangun Smart Chip Audio Organic Growth System sebagai Input Device Pembukaan Stomata pada Pemupukan Daun Tanaman Perkebunan: Nur Kadarisman, Wipsar S.B. Dwandaru, Purwanti W Hastuti - Nur Kadarisman, Nur Kadarisman; Wipsar Sunu Brams Dwandaru, Wipsar Sunu Brams Dwandaru; Purwanti Widhy Hastuti, Purwanti Widhy Hastuti (Jurnal Fisika dan Aplikasinya, 2025)
The application of acoustic wave technology for agriculture purposes may be used to strengthen the food persistency in the society. The creation and modification of audio technology, which is in this case, the audio organic growth system (AOGS) combined with foliar fertilization and audio intensity variable optimization has been applied to increase the quality and productivity of plantation crops. The AOGS system is mainly used as an input device in the leaf stomata opening of plantation crops. However, the main obstacle in the application of AOGS is the electronic devices which are not practical and compatible. Moreover, the AOGS instrument which consists of an audio player and a speaker turns out to be quite heavy. Hence, in this research, a smart chip AOGS (SC-AOGS) has been produced equipped with components of TDA2003 as an audio amplifier, WT5001 as a storage and audio player, ATMega328 16 MHz as a processor, a speaker as an output source of the sound, and a matrix LCD with dimension of 16 × 2 that produces output frequency source display. Moreover, the SC-AOGS instrument is also equipped with sound volume setting. The SC-AOGS instrument is quite easy to use and compatible, hence may overcome the problem of the AOGS system.